A Systematic Review: The Role of Parent-Child Relationship and Parental Emotional Socialization on Children’s Emotion Regulation - Farhah Suruurah Rizqiah Sanaky; Riana Sahrani; Fransisca Iriani Roesmala Dewi (Buletin Psikologi, 2026)
Children’s emotion regulation is a crucial aspect of their socioemotional development which is influenced by the parent-child relationship and parental emotion socialization behavior (ESB). Emotion regulation refers to an individual’s ability to manage their emotions. Parent-child relationship is a whole dynamic of characters in the family, consisting of both nurture and protective behavior from parents to children. Parental ESB is defined as the way parents respond to their child’s expressed emotions. Previous literature has found that these variables are interrelated, but most studies have only examined one or two variables, and rarely have they examined all three variables simultaneously. Therefore, this study aims to explore the role of parent-child relationship and parental ESB on children's emotion regulation. This study used systematic review method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines, with literature searches conducted across six databases: APA PsycNet, SAGE Open, MDPI, Taylor & Francis, PubMed, and ScienceDirect. Studies published between 2016 and 2025 were included. Eligible participants were healthy married parents and their healthy children ages 3-11 years. Inclusion criteria comprised English or Indonesian quantitative or qualitative studies published in Q1-Q4 indexed journals with open-access full texts. Studies published before 2016, lacking full-text access, or involving participants other than parent or teachers were excluded. The search yielded 44.837 articles and after screening, 7 articles were identified as meeting the objectives of this study. The data collected by synthesizing the contents of the 7 research articles that met the selection criteria. Findings show that the parent-child relationships and parental ESB play role in children’s emotion regulation. Additional factors that influence parental ESB and children’s emotion regulation were also identified. The findings contribute to the literature of developmental, family and educational psychology by providing additional evidence on children’s emotion regulation, parent-child relationship and parental ESB, while further strengthening the existing theoretical frameworks. The practical implications of this research were implemented through a community service program (Pengabdian Kepada Masyarakat (PKM)) seminar conducted at Kindergarten X in West Jakarta, with the parents of the students as the audience. The seminar addressed the importance of understanding how to respond to children’s emotions and how to build a supportive relationship with their child.